국내 다문화 청소년의 사회적 건강결정요인: 통합적 문헌고찰(2018~2020) - 김유림(Kim, Youlim); 이현경(Lee, Hyeonkyeong); 이혜연(Lee, Hyeyeon); 이미경(Lee, Mikyung); 김수경(Kim, Sookyung); Kennedy Diema Konlan (지역사회간호학회지, 2021)
Purpose: This study is an integrated literature review to analyze health problems and social determinants of multicultural adolescents in South Korea. Methods: An integrative review was conducted according to Whittemore & Knafl's guideline. An electronic search that included publications from 2018 to 2020 in the PubMed, EMBASE, Cochrane Library, CINAHL, RISS, and KISS databases was conducted. Of a total of 67 records that were identified, 13 finally met full inclusion criteria. Text network analysis was also conducted to identify keywords network trends using NetMiner program. Results: The health problems of multicultural adolescents were classified into mental health (depression, anxiety, suicide and acculturative stress) and health risk behaviors (smoking, risky drinking, smartphone dependence and sexual behavior). As social determinants affecting the health of multicultural adolescents, the biological factors such as gender, age, and visible minority, and the psychological factors such as acculturative stress, self-esteem, family support, and ego-resiliency were identified. The sociocultural factors were identified as family economic status, residential area, parental education level, and parents' country of birth. As a result of text network analysis, a total of 41 words were identified. Conclusion: Based on these results, mental health and health risk behaviors should be considered as interventions for health promotion of multicultural adolescents. Our findings suggest that further research should be conducted to broaden the scope of health determinants to account for the effects of the physical environment and health care system.